2011
DOI: 10.1200/jop.2011.000399
|View full text |Cite
|
Sign up to set email alerts
|

Donating Tissue for Research: Patient and Provider Perspectives

Abstract: This article illustrates common patient and provider concerns about donating tissue for the purpose of research, discusses best practices, and provides answers to common patient questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Reassuringly, only 7 % of our patients had concerns about the use and storage of blood/tissue samples for research, and indeed, many patients strongly felt that this was not an issue. This is supported by the results of other studies, which demonstrate that the majority of cancer patients would allow the use of their tissue for research [ 13 , 24 , 25 ]. In our survey, 78 % of patients would agree to donate tissue for genetic research, even if they were not told their genetic results, indicating patient support for genomic research into cancer.…”
Section: Discussionsupporting
confidence: 76%
“…Reassuringly, only 7 % of our patients had concerns about the use and storage of blood/tissue samples for research, and indeed, many patients strongly felt that this was not an issue. This is supported by the results of other studies, which demonstrate that the majority of cancer patients would allow the use of their tissue for research [ 13 , 24 , 25 ]. In our survey, 78 % of patients would agree to donate tissue for genetic research, even if they were not told their genetic results, indicating patient support for genomic research into cancer.…”
Section: Discussionsupporting
confidence: 76%
“…More detailed consent forms/processes are required for biospecimen collection trials, and an ECOG study showed that a more detailed consent form increased trial participation (35). Patients appreciate being given detailed information on how their biological specimens will be stored and potentially used in the future for additional research.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that therapeutic benefit could also override trust issues in minorities [11]. Moreover, similar to behavior in non-minority groups [37,38], among minorities already enrolled in a study, most would be willing to provide specimens [5, 11, 39]. Non-invasive methods of biospecimen collection may also favor the participation of Latinos (and others) in biomedical research.…”
Section: Discussionmentioning
confidence: 99%